Comparison of two nonsteroidal antiinflammatory drugs with short and long plasma half- lives with regard to their efficacy and safety: a randomized placebo controlled double-blind study. (Annals of Medical Research, 2021)
None
Keywords: s : NSAIDs, Diclofenac, Tenoxicam, Osteoarthritis.